The association between overuse and musculoskeletal injuries and the female athlete triad in Division I collegiate athletes - Olson, E. M.; Sainani, K. L.; Dyrek, P.; Bakal, D.; Miller, K.; Carlson, J. L.; Fredericson, M.; Tenforde, A. S. (PM&R, 2024)
Introduction Although the female athlete triad (Triad) has been associated with increased risk of bone-stress injuries (BSIs), limited research among collegiate athletes has addressed the associations between the Triad and non-BSI injuries.